Safety surveillance after BNT162b2 mRNA COVID-19 vaccination: results from a cross-sectional survey among staff of a large Italian teaching hospital - Vigezzi, Giacomo Pietro; Lume, Alessandra; Minerva, Massimo; Nizzero, Paola; Biancardi, Anna; Gianfredi, Vincenza; Odone, Anna; Signorelli, Carlo; Moro, Matteo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Comirnaty® was the first COVID-19 vaccine available for the vaccination campaign of healthcare workers in Italy. With the aim of assessing vaccine safety, we conducted a cross-sectional survey administrating a voluntary-based questionnaire on adverse events following immunisation (AEFIs) in San Raffaele Hospital, Milano, Italy.Methods: From 4th January 2021 to 27th April 2021, we collected 2,659 questionnaires (response rate: 24,5%). We analyzed data, reporting AEFIs by gender, age, self-reported severity, type, time of insurgence and duration, and estimating relative-risk ratios (RRR) and corresponding 95% confidence intervals (CI).Results: The most reported symptoms were injection site pain, fatigue, headache, myalgia, chills, fever, and arthralgia. Severe systemic reactions were more frequent after receiving the second dose (RRR 6.25, 95% CI 4.57-8.55), in women (RRR 3.33, 95% CI 2.30-4.82), and less frequent in individuals aged 60 or more (RRR 0.26, 95% CI 0.14-0.49). In addition, we noted a wide range of adverse events of special interest (AESIs).Conclusions: Consistently with clinical trials and pharmacovigilance surveillance, AEFIs were frequent, but severe ones were uncommon, supporting the massive implementation of the COVID-19 vaccination campaign and providing valuable data for a risk profiling of vaccinees. (www.actabiomedica.it)